Biofuels as alternative energy source for shipping industry : a feasibility study on bio-methanol on marine application - Ho, Tsui Wan (2019)
In the past two centuries, the shipping industry has witnessed changes to propulsion systems of ocean-going vessels for commercial trade. From a series of innovation of the diesel engine, heavy fuel oil (HFO) has become a fuel of choice for shipping industry since 1970 due to its applicability, cost-efficiency, and ease of handling. Currently, for commercialized shipping, there are more than 93,000 ocean-going vessels used for cargo movement with different types and fleet age. The number of ships in the industry is bound to increase due to the growth of population and globalization. The annual fuel consumption of ships is around 2-4%. Against the progressive transformation of other industries and recent developments, there is a rising concern over the sustainability of current practice of ship operation using conventional fuel oils, particularly concerns over GHG emission. As environmental demands on the marine industry are getting tougher, with more stringent regulations in place, there is a need for the industry to change to meet regulatory standards. Towards energy and environmental sustainability, worldwide research and development have been focusing on alternative sources of energy for the adoption of ships. One potential option is to consider the application of lower-carbon energy sources such as biofuels, also known as alternative fuels. Biofuels have become an explored option to resolve this challenge of decarbonization of the shipping industry. Different types of biofuels may have different technical, environmental, economic performances which would affect the overall operation of ships. This research project describes an assessment of the feasibility of bio-methanol as an alternatives source of energy for the marine application. The assessment is based on certain criteria, which includes environmental, economic, safety, supply and distribution considerations regarding the use of methanol as a sustainable fuel source for commercial vessels. Methanol can be made up of both fossil-based and biomass-based. From a safety perspective of methanol usage onboard ships, there were no barriers identified. The cost of methanol, in general, is higher than that of using HFO, which could be a potential barrier that hinders the adoption of such fuel within the shipping industry. However, given that regulatory measures requiring the reduction in GHG emissions from ships could favor the uptake of bio-methanol reducing the economic barrier as the implementation of other alternative solutions would incur substantial costs. An economic analysis was conducted using methods of NPV and payback period. Bio-methanol is found to be not economically feasible without any price intervention such as bunker levy. More research can be initiated on the means to bridge the economic gap of using bio-methanol.